Community media for reconciliation: a Cypriot case study - Carpentier, Nico; Doudaki, Vaia (My University, 2014)
Community media studies have often neglected how community media can contribute inareas ridden with conflict to more peaceful ways of cohabitation. This article aims to lookin detail at how the Cyprus Community Media Centre (CCMC) has developed conflictresolution strategies to reduce the antagonism in the Cypriot society, an island divided since1974. Then it looks at the problems and complexities that this organization has to facewhen trying to realize its remit, caused by the fallacies in the community media model andby the Cypriot context of conflictuality. Despite the difficulties, the CCMC illustrates thatcommunity media can play a role in conflict resolution, creating more opportunities formutual understanding and for the humanization of the other.
Keywords: Community media; Cyprus